Role of Small RNAs in Trypanosomatid Infections - Linhares-Lacerda, Leandra; Morrot, Alexandre (Frontiers in Microbiology, 2016)
Trypanosomatid parasites survive and replicate in the host by using mechanisms that aim to establish a successful infection and ensure parasite survival. Evidence points to microRNAs as new players in the host-parasite interplay. MicroRNAs are small noncoding RNAs that control proteins levels via post-transcriptional gene down-regulation, either within the cells where they were produced or in other cells via intercellular transfer. These microRNAs can be modulated in host cells during infection and are among the growing group of small regulatory RNAs, for which many classes have been described, including the transfer RNA-derived small RNAs. Parasites can either manipulate microRNAs to evade host-driven damage and/or transfer small RNAs to host cells. In this mini-review, we present evidence for the involvement of small RNAs, such as microRNAs, in trypanosomatid infections which lack RNA interference. We highlight both microRNA profile alterations in host cells during those infections and the horizontal transfer of small RNAs and proteins from parasites to the host by membrane-derived extracellular vesicles in a cell communication mechanism.